2001
DOI: 10.2166/wqrj.2001.027
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Microtox® Toxicity Test System for Assessing the Toxicity of Sediments and Soils

Abstract: Use of Microtox for screening sediment or soil samples from contaminated systems either alone or in combination with a battery of other tests is supported by an ever-increasing number of comparative studies demonstrating its utility, sensitivity, rapidity and affordability. Organic solvent extracts and direct solidphase material provide an assessment of the potential toxicity exerted by both dissolved and bound contaminants. In contrast, tests utilizing pore water or elutriates may be limited to assessing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 103 publications
(158 reference statements)
1
43
0
3
Order By: Relevance
“…Furthermore, the stabilization treatment not only reduced the acute toxicity completely but also actually caused stimulation (increased bioluminescence) in the bioassay. This bioassay is a good tool to evaluate general toxicity in the environment and the results are consistent with toxicity to soil and sediment invertebrates (Doherty, 2001).…”
Section: General Evaluationsupporting
confidence: 63%
“…Furthermore, the stabilization treatment not only reduced the acute toxicity completely but also actually caused stimulation (increased bioluminescence) in the bioassay. This bioassay is a good tool to evaluate general toxicity in the environment and the results are consistent with toxicity to soil and sediment invertebrates (Doherty, 2001).…”
Section: General Evaluationsupporting
confidence: 63%
“…It has often been stated that only the free (dissolved) pool of an adsorptive pollutant is actually bioavailable and thus able to impose a toxic effect on the soil organisms (8,24). On the other hand, many recent reports have suggested that the adsorbed pollutant pool may also be at least partially available for the microorganisms, both in terms of causing toxic effects (2,3,16,(38)(39)(40) and serving as substrates for biodegradation (26,27). As amended LAS is primarily adsorbed to soil particles in the present soils (I.…”
Section: Vol 68 2002 Bioluminescent N Europaea Reporter Of Las Toxmentioning
confidence: 99%
“…The toxicity of the oil-treated-sediments was assessed with two regulatory biotests: the Microtox 1 Solid Phase Test (SPT), which can be used to determine the acute toxicity of sediment, and an amphipod (Hyalella azteca) bioassay, which measures the lethal and sublethal toxicity of sediments. The Microtox 1 test has been used widely over the past two decades for toxicity assessment of soil and sediments (Cook and Wells, 1996;Bombardier and Bermingham, 1999;Doberty, 2001;Lee et al, 2003b), and the Microtox 1 SPT has been used successfully to evaluate the efficacy of oil spill remediation strategies (Lee et al, 1995(Lee et al, , 2003b. Likewise, amphipod survival (e.g., Hyalella azteca, Eohaustorius esturius) has been often used to evaluate sediment toxicity in recent years (Ingersoll et al, , 1996Kemble et al, 1994Kemble et al, , 1998Kemble et al, , 1999Bhattacharyya et al, 2003;Blaise et al, 2004).…”
Section: Introductionmentioning
confidence: 99%